Implementasi Teknologi pada Pembelajaran Anak Usia Dini - Munir, Misbahul Munir; Subaeri, Abdul Holik (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
This research is aimed to obtain an overview of the implementation of the use of technology in learning in early childhood. In research, qualitative method is used with a literature review research approach or literature or library study. Some of the data sources used are textbooks, scientific journals and statistical references, research results in the form of theses, theses, dissertations, and the internet as well as other appro-priate sources. The information collected then analyzes the data to draw conclusions to get correct and accu-rate results when analyzing the data through content analysis. The research results show that at the PAUD level, the use of technology in the learning process is possible. There are technological tools that are easily adapted for this and help children in moral development, motor skills, cognitive abilities, language acquisition and social learning. In connection with its application, technology can have both positive and negative impacts. If the use of technology is not properly monitored, the positive effects can become negative because technology can be used in the classroom or at home. Therefore, teachers are expected to be able to make maximum use of technology in the classroom, requiring training and support from the relevant government.